The use of the DEA method for simultaneous analysis of the interrelationships among economic growth, environmental pollution and energy consumption - Christina Bampatsou; George Hadjiconstantinou (International Journal of Economic Sciences and Applied Research, 2009)
In this study Data Envelopment Analysis (DEA) is used not only to develop an efficiency index which combines economic activity, CO2 emissions and energy consumption of the production process in the 31 countries of Europe for the year 2004, but also to make estimates about the margins of long term increase or decrease in the consumption levels of exhaustible energy resources of a selected sample (Switzerland, Greece, United Kingdom, and Luxembourg) of European countries (out of 31) which belong to the high income group of OECD members.As shown, each country can achieve better TE when its increased economic activity is combined with improved ecological performance. It can be noticed from the analysis that the developed economies that tend to stabilize their environmental degradation through time (Switzerland), as the GDP (per capita GDP) increases, ensure satisfactory margins for the increase in the consumption of the dirty energy index (DEI) in the long term, and thus contribute to sustainableeconomic development. This fact is significantly different in countries showing either intense deterioration (Greece) or temporary improvement (United Kingdom, Luxemburg) in the pollution levels without any indications of a temperate stabilization of environmental degradation.
Keywords: Q01; Q32; 330; technical efficiency index; sustainability; energy consumption; environmental pollution; economic development; DEA; future estimations